The impact of synoptic storm likelihood on European subseasonal forecast uncertainty and their modulation by the stratosphere ... - Rupp, Philip; Spaeth, Jonas; Gerstman Afargan, Hilla; Büeler, Dominik; Sprenger, Michael; Birner, Thomas (ETH Zurich, 2024)
Weather forecasts at subseasonal-to-seasonal (S2S) timescales have little forecast skill in the troposphere: individual ensemble members are mostly uncorrelated and span a range of atmospheric evolutions that are possible for the given set of external forcings. The uncertainty of such a probabilistic forecast is then determined by this range of possible evolutions - often quantified in terms of ensemble spread. Various dynamical processes can affect the ensemble spread within a given region, including extreme events simulated in individual members. For forecasts of geopotential height at 1000 hPa (Z1000) over Europe, such extremes are mainly comprised of synoptic storms propagating along the North Atlantic storm track. We use ECMWF reforecasts from the S2S database to investigate the connection between different storm characteristics and ensemble spread in more detail. We find that the presence of storms in individual ensemble members at S2S timescales contributes about 20 % to the total Z1000 forecast ... : Weather and Climate Dynamics, 5 (4) ...